Paying for Sex Among Males and Females: A Cross-Sectional Survey in Melbourne, Australia. Issue 3 (March 2021) - Chow, Eric P.F.; Hocking, Jane S.; Bradshaw, Catriona S.; Phillips, Tiffany R.; Tabesh, Marjan; Donovan, Basil; Maddaford, Kate; Chen, Marcus Y.; Fairley, Christopher K.
Abstract : Paying for sex is more common among bisexual males, followed by heterosexual males then homosexual males, but rare among females attending a sexual health clinic in Melbourne, Australia. Abstract : Background: Most research focuses on individual selling sex but very few on paying for sex. This study aimed to determine the proportion of males and females who paid for sex and associated factors. Methods: We conducted a short survey at the Melbourne Sexual Health Centre between March and April 2019, which included a question on whether they had paid for sex in the past 3 months. The proportion of individuals who had paid for sex was calculated by sex and sexual orientation. Univariable and multivariable logistic regression models were conducted to identify individual's factors (e.g., demographics, sexual orientation, and HIV/sexually transmitted infection [STI] positivity) associated with paying for sex in the past 3 months. Results: The proportion who reported paying for sex in the past 3 months was 12.2% (42/345) among heterosexual males, followed by 6.4% (23/357) among men who have sex with men (MSM) and 0.2% (1/430) among females. HIV status, preexposure prophylaxis use, and sexual orientation were not associated with paying for sex among MSM. No MSM living with HIV reported paying for sex in the past 3 months. There was a significant association between paying for sex and gonorrhea (odds ratio, 2.84; 95% confidence interval, 1.05–7.71; P = 0.041) but not HIV, syphilis, and chlamydia among MSM. HIV/STI was not associated with paying for sex among heterosexual males. Conclusions: Paying for sex was more commonly reported among heterosexual males, followed by MSM. Females were very unlikely to pay for sex. There was a limited association between HIV/STI diagnosis and paying for sex among males.